Kinerja ESG dan nilai perusahaan: Financial slack sebagai moderasi - Reynaldi Dharmawan; Aurora Angela (LPMP Imperium, 2026)
Firm value reflects market perceptions of a company’s strategic decisions, including ESG performance and financial flexibility. This study examines the effect of ESG performance on firm value and investigates the moderating role of financial slack in the ESG–firm value relationship, which constitutes the novelty of this research. The sample comprises 106 firms listed on the Refinitiv Eikon during 2020–2024 with ESG scores. The results indicate that ESG performance does not have a significant effect on firm value, while financial slack has a positive and significant direct effect. However, the interaction between ESG performance and financial slack is not statistically significant, suggesting that financial slack does not strengthen the impact of ESG performance on firm value. These findings imply that financial flexibility plays a more immediate role in enhancing firm value than ESG performance within the observed period, and that excess financial resources do not necessarily increase the market’s valuation of ESG activities. Public interest statements This study implications for companies indicate that ESG performance does not guarantee increased company value in the short term. However, ESG still needs to be considered as part of a long-term strategy, as it can contribute to reputation, operational sustainability, risk management, and future regulatory compliance. The implications for the public and investors indicate that investors cannot rely solely on ESG scores in making short-term investment decisions; portfolio selection should still consider fundamental factors such as profitability, liquidity, and funding structure.